2020
DOI: 10.1136/bmjgh-2020-003675
|View full text |Cite
|
Sign up to set email alerts
|

Protecting essential health services in low-income and middle-income countries and humanitarian settings while responding to the COVID-19 pandemic

Abstract: In health outcomes terms, the poorest countries stand to lose the most from these disruptions. In this paper, we make the case for a rational approach to public sector health spending and decision making during and in the early recovery phase of the COVID-19 pandemic. Based on ethics and equity principles, it is crucial to ensure that patients not infected by COVID-19 continue to get access to healthcare and that the services they need continue to be resourced. We present a list of 120 essential non-COVID-19 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 8 publications
3
67
0
Order By: Relevance
“…In resource -constrained contexts where the burden of disease and risk factors are often distributed unevenly in the population, factors such as siloed nancing and fragmented governance of the health system may well have contributed to an increased burden on the poor [15]. Today, service providers and policy-makers worldwide are pressured to decide which essential services must be protected as precious resources are reallocated [16]. Making sound decisions is even more di cult in a context where political, economic or nancial interests might well result in fragmented directives that privilege the powerful and thus serve to increase inequities [15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In resource -constrained contexts where the burden of disease and risk factors are often distributed unevenly in the population, factors such as siloed nancing and fragmented governance of the health system may well have contributed to an increased burden on the poor [15]. Today, service providers and policy-makers worldwide are pressured to decide which essential services must be protected as precious resources are reallocated [16]. Making sound decisions is even more di cult in a context where political, economic or nancial interests might well result in fragmented directives that privilege the powerful and thus serve to increase inequities [15].…”
Section: Resultsmentioning
confidence: 99%
“…It has been recognized that around the world the poor are experiencing more severe direct and indirect consequences of Covid-19. To disregard the short-and long-term effects of the pandemic may have costly impacts on the society overall, as Covid-19 is affecting both the demand for and the provision of essential services [15][16][17]. A one size ts all response is likely to cause great hardship for those most in need.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On value-for-money grounds, basic cardiovascular disease prevention and care are just as 'essential' as immunisation programmes, maternal healthcare and screening and treatment of HIV infection. 6 At the same time, locations with advanced cardiovascular care systems need guidance on how to balance the need to treat severe cardiovascular disease against the need to adapt quickly to increased COVID-19 caseloads. Ball et al found that emergency department visits and percutaneous coronary intervention procedure rates in UK hospitals had partially rebounded by the end of May 2020.…”
Section: Editorialmentioning
confidence: 99%
“…In recognition of this vulnerability, Blanchet et al. ( 7 ) identified the prevention of cardiovascular disease as a health system priority that should be unconditionally preserved despite the pandemic, based on their assessment of the magnitude of harm that would arise from its interruption. Even in the midst of the pandemic, clinicians can evaluate patient risk by telephone or video.…”
mentioning
confidence: 99%